Proportionate income differentials: a long walk to social justice. A case study on the Entgeltrahmenabkommen (ERA) Baden-Wuerttemberg, a general agreement on pay grades, that seeks to achieve pay equity in this region of the German metal and electrical industry and a critical evaluation of how this model can assist in the implementation of section 27 of the Employment Equity Act (EEA) of South Africa - Helm, Heinrich (Department of Commercial Law, 2018)
Vertical income differentials between occupational levels in South Africa are among the highest in the world. Under apartheid skilled work performed predominantly by white employees was artificially overvalued, while unskilled work performed predominantly by black employees was systematically undervalued. These discriminatory social and legal norms laid the foundation for the existent disproportionate income differentials. The post apartheid government headed by Nelson Mandela acknowledged the existence of the apartheid wage gap. They were mindful that the vertical pay gap need not only be ‛deracialized', but needs to be eradicated. In this regard the South African Constitution of 1996 and the Employment Equity Act of 1998 (EEA) underpins the demand for non-discriminatory pay structures. Section 27 of the EEA was enacted to address disproportionate income differentials, but has not yet been adequately implemented. The purpose of this thesis is to consider whether the Entgeltrahmenabkommen (ERA) (a general agreement on pay grades) which resulted in the redesign of the pay structure in the German metal and electrical industry correcting long-standing pay differentials between socalled blue and white collar workers, can add value to the implementation of section 27 of the EEA. The thesis consists of six chapters. After the introduction chapter, chapters 2 and 3 consider the historical and current context of income inequality in South Africa; and chapters 4 and 5 provide a detailed analysis of the ERA in Germany and the recommendations that derive from the ERA. Chapter 6 concludes the thesis. There are important lessons to be derived both from the drafting and the implementation phases of the ERA. The ERA process revealed that being conscious of the different challenges that might arise in each phase is a prerequisite for success. The development of norms and benchmarks in the drafting phase minimised pay discrimination. The implementation phase of the ERA showed that prejudicial views and attitudes can hinder the complete eradication of discriminatory payment practices if sufficient heed is not paid to their strong influential role. This thesis concludes that the lessons derived from the implementation of the ERA can assist in introducing proportionate vertical income differentials as required by section 27 of the EEA.